2008
DOI: 10.1016/j.eurpsy.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Specialist training in psychiatry in Europe – Results of the UEMS-survey

Abstract: According to the aim of the Treaty of Rome from 1957 which postulated the free movement of workers throughout the European Union, the European Board of Psychiatry in the UEMS (European Union of Medical Specialists) carried out a comprehensive survey of training in psychiatry, including all member countries in order to evaluate the present state of training in psychiatry in each. The survey should indicate whether the training requirements [UEMS Section Psychiatry. Charter on training of medical specialists in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 4 publications
5
42
1
3
Order By: Relevance
“…Thus, we consider training programmes in Europe to be broadly compatible with one another and that significant progress has been made towards harmonisation of psychiatric trainees' curricula in Europe. These findings are consistent with those from previous studies (Lotz-Rambaldi et al 2008;Oakley & Malik 2010). It should be noted, however, that some countries do not yet offer important subspecialties in old age or liaison psychiatry.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, we consider training programmes in Europe to be broadly compatible with one another and that significant progress has been made towards harmonisation of psychiatric trainees' curricula in Europe. These findings are consistent with those from previous studies (Lotz-Rambaldi et al 2008;Oakley & Malik 2010). It should be noted, however, that some countries do not yet offer important subspecialties in old age or liaison psychiatry.…”
Section: Discussionsupporting
confidence: 83%
“…Recommendations were made for the structure of training programmes, competency-based training standards, standards for training institutions, trainers and supervisors, and quality assurance mechanisms (UEMS Section for Psychiatry 1997; Table 1). In a follow-up survey, the UEMS members evaluated the extent of the implementation of their recommendations (UEMS Section for Psychiatry 1997) and found that these were met only in part (Lotz-Rambaldi et al 2008). The results from subsequent surveys further confirmed differences amongst training programmes throughout Europe (Karabekiroglu et al 2006;Oakley & Malik 2010).…”
Section: Introductionmentioning
confidence: 99%
“…2 Towards this aim, several surgical specialties have already established accreditation and examination procedures that are recognised throughout the EU. 3 In 1992, the Psychiatric Trainees' Committee of the Royal College of Psychiatrists facilitated a meeting of European trainees and representatives from nine European countries convened in London.…”
mentioning
confidence: 99%
“…Young child and adult psychiatrists are often ambivalent about which career to pursue, clinical or research one, and this underscores even more the need for obtaining the information and skills during the residency training. In Europe, there is a paucity of the curriculum with regard to acquiring research skills and information on pursuing a research career in both child and adult psychiatry [3,4]. In this context, we report a new educational initiative at the Department of Child and Adolescent Psychiatry at Medical University of Vienna, Austria.…”
mentioning
confidence: 99%